The 'new left' and democractic governance in Latin America - Arnson, Cynthia J....[et al.] (Woodrow Wilson International Centre for Scholars. Latin American Program WashingtonUS, 2007)
Seeks to understand why so many governments of the Left have come to power in Latin America at this particular moment in the region's history. Explores the impact of specific public policies in the areas of social welfare, citizen participation, human rights and foreign relations.